Sense of coherence as a mediator of health-related quality of life dimensions in patients with breast cancer: a longitudinal study with prospective design. Issue 1 (December 2015) - Rohani, Camelia; Abedi, Heidar-Ali; Sundberg, Kay; Langius-Eklöf, Ann
Abstract Background In our previous study, we found that the degree of sense of coherence (SOC) and baseline ratings of several dimensions of health-related quality of life (HRQoL) were the most important predictors of HRQoL changes 6 months after the pre-diagnosis period of breast cancer. To find a way to explain these findings, the aim of this study was to explore the mediating effect of the SOC between ratings of HRQoL dimensions before final diagnosis, and ratings of the same dimensions at the 6 months follow up, within a sample of women with breast cancer. Methods A longitudinal study with a prospective design at baseline (T1) and 6 months later (T2) was conducted on 162 women with breast cancer. To measure HRQoL dimensions three different questionnaires, the European Organization for Research and Treatment of Cancer QLQ-30, the SF-12 Health Survey version 2 and the Health Index were applied at T1 and T2 to cover both diagnostic-specific and generic dimensions. Measurement of the SOC as a mediator was done by the SOC-13 scale. Results Mediational analyses on eight significant pairs of HRQoL dimensions showed that the degree of SOC totally mediated variations of global quality of life (p  < 0.001) as well as cognitive and social functioning (p <0.05) scores between T1 to T2. Changes in the scores of emotional functioning (p  < 0.01), fatigue (p  < 0.05), financial difficulties (p  < 0.05), well-being (p  < 0.001), and mental health component (p  < 0.001) were partially mediated. The degree of SOC explained 16 % to 45 % of the variances in HRQoL dimensions at T2. Conclusions The mediating pathway of the SOC in the context of this study appears to be the key to understanding how a higher sense of coherence as an inner resource may serve as a protective psychological factor in the adaptation process of the patients. Clinicians might consider coherence-oriented structure of the SOC and the connection between the SOC and HRQoL data in intervention plans from the first visit onwards. It may assist the identification of women who are at greater risk for maladaptation to the breast cancer trajectory.